1980
DOI: 10.1177/028418518002102a07
|View full text |Cite
|
Sign up to set email alerts
|

Selective Vein Catheterization for Hormone Assay in Endocrine Tumours of the Pancreas

Abstract: Based on 45 examinations the technique of selective catheterization of the pancreatic veins for blood sampling using percutaneous transhepatic approach to the portal vein is described. The results are compared with the angiographic findings in 16 patients with islet cell tumours of islet cell hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Although no side effects were encountered in our series, the following major complications are reported in the literature: large hematoma of the liver in 1 case, fever and pain following accidental puncture of the gallbladder in 1 case, bile leakage requiring cholecystostomy in 1 patient, intraabdominal bleeding requiring operative intervention in 1 patient, and mesenteric vein thrombosis in another [21,[28][29][30].…”
Section: Discussionmentioning
confidence: 97%
“…Although no side effects were encountered in our series, the following major complications are reported in the literature: large hematoma of the liver in 1 case, fever and pain following accidental puncture of the gallbladder in 1 case, bile leakage requiring cholecystostomy in 1 patient, intraabdominal bleeding requiring operative intervention in 1 patient, and mesenteric vein thrombosis in another [21,[28][29][30].…”
Section: Discussionmentioning
confidence: 97%
“…When arteriography fails, percutaneous transhepatic portal and pancreatic venous sampling with measure ment of peptide gradients may localize areas of high concentration [2,27], This method is however technically difficult and interpreta tion of data frought with problems because of the variability in pancreatic venous drainage and lack of information on normal peptide concentrations. Complications include perfo ration of the gall-bladder and hepatic haematomas; however, in experienced hands, this technique is a useful adjunct to arteriography [27].…”
Section: Localization O F Tumoursmentioning
confidence: 99%
“…Some authors have suggested that venous sampling along the splenic, superior mesenteric, and portal veins yields results comparable to the more selective sampling of the pancreatic veins, which is a more time consuming procedure [MI. However, the presence of laminar flow in the portal vein and its larger tributaries may produce false results [37], thus making nonselective venous sampling a less desirable procedure [41,43,45]. Sampling of the hepatic veins has no value for either the evaluation of the results of pancreatic venous sampling or the detection of hepatic metastases, for which angiography is a more sensitive method [37].…”
Section: Computed Tomographymentioning
confidence: 99%